Fluid mechanics of flow through microchannels - Navid Kashaninejad (2013)
The main objective of this thesis is to characterize and investigate single-phase liquid flow in microchannels, and can be divided into two parts: analytical modeling and experimental investigation. In the analytical part, velocity distribution and Darcy friction factor of liquid flow in both parallel-plate and rectangular microchannels were revised theoretically by taking into account the effects of slip boundary conditions as well as the aspect ratio of the channels.